Maize root growth under regular water content, subjected to compaction, irrigation frequencies, and shear stress (2016)
Maize (Zea mays L.) is an agricultural crop grown in the incompressible and alterable savanna soils, which are, with no trouble, compacted by machinery, consolidated by drying and wetting, and insufficiently irrigated. The objectives were to study the effects of: (a) water content and compaction over root length, root penetration and root volume under soil water content requirements, and (b) shear stress, and normal tension on root growth. The methods were: Proctor test, water meters, watering frequency, 30x30x1.5 cm plastic cylinders, randomized block designs and factorial simple treatment, four compaction levels per layer (0, 12, 24 and 36), four soil water contents with four irrigation frequencies (daily, inter-day, every two days and every three days) and water amount of 10% to 13% with mean value of 11.78%. Among the findings: (a) The root length average 74.07 cm, (b) Root penetration with median rate 20.42 cm, (c) Root volume median rate 49.601 cm3. In conclusion, maize root structure was positively influenced by water content more than compaction; the dependent variables root length and volume showed no significant difference in the independent variables studied and root penetration presented significance in irrigation treatments